Mengoptimalkan Pembelajaran Dengan Pendekatan TaRL Untuk Meningkatkan Motivasi Belajar di SD Negeri Condongcatur Sleman - Pin Harjanti; Ayub Prastiyo (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Effective learning requires an approach that can increase students' motivation to learn and engagement in learning. One innovative approach that has been proven effective in this regard is Teaching at the Right Level (TaRL). Teaching at the Right Level (TaRL) focuses on matching learning materials to students' ability levels, not just age or grade. Research shows that this approach can optimize materials that match learners' abilities and can further increase learners' motivation to learn. By grouping learners according to ability and providing appropriate learning support, Teaching at the Right Level (TaRL) becomes a learning solution for learners based on ability level to overcome learning differences and increase learners' confidence. This research contains the basic concepts of Teaching at the Right Level (TaRL), supporting theories and the impact of the implementation of learning with the Teaching at the Right Level (TaRL) approach on students' learning motivation at SD Negeri Condongcatur. Teaching at the Right Level (TaRL) increases learners' engagement and satisfaction in learning. Teaching at the Right Level (TaRL) is an effective approach to increase learners' learning motivation.